Soal Matematika Berbasis Higher Order Thinking Skills (HOTS) : Studi Pengembangan Dengan Fokus Pada Permasalahan Sampah - Maratul Hamidah; Alhaq, Arini; Farida, Farida (Griya Journal of Mathematics Education and Application, 2025)
This research develops mathematics questions based on Higher Order Thinking Skills (HOTS) specifically designed to enhance students' higher-order thinking abilities through the context of waste problems. The purpose of this research is to develop HOTS-based mathematics questions within the context of waste issues. This study employs the Research and Development method using the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The development stage involves nine validators, consisting of subject matter experts, question experts, and media experts. The implementation stage involves 38 students divided into two groups. Validity, reliability, distinguishing power, and difficulty level of the mathematics questions are tested by having students work on the developed HOTS questions. The assessment of the practicality of the mathematics questions based on HOTS is conducted through student response questionnaires. The validation results from the nine validators indicate criteria of "Very Worthy to Use." The content validity tests are considered valid and reliable, resulting in difficulty levels and distinction powers that meet the criteria. The practicality trial of the mathematics questions based on HOTS with the context of waste issues received "very strong" criteria among the students. Based on these results, it can be concluded that the HOTS-based mathematics questions with the context of the waste problem as many as 20 questions are valid, practical, and suitable for use, because they have met the five requirements or characteristics of good questions, namely validity, reliability, objectivity, practicability and economy.